25.2k views
4 votes
Please help me with this, thanks :’)Please provide step-by-step explanation if possible

Please help me with this, thanks :’)Please provide step-by-step explanation if possible-example-1
User SteveJ
by
5.4k points

1 Answer

6 votes

Simplify the expression.


\begin{gathered} -(2)/(3)p+(1)/(5)-1+(5)/(6)p=-(2)/(3)p+(5)/(6)p+(1)/(5)-1 \\ =(-2\cdot2p+5p)/(6)+(1-1\cdot5)/(5) \\ =(-4p+5p)/(6)+(1-5)/(5) \\ =(1)/(6)p-(4)/(5) \end{gathered}

So equivalent expression is,


(1)/(6)p-(4)/(5)

User Eprst
by
4.6k points